The sociology of children, childhood and generation - Leonard, Madeleine; Rojek, Chris (Los Angeles SAGE, 2016)
"This book illustrates sociology's distinctive contribution to childhood studies and to understanding contemporary children and childhood. By focusing specifically on the ongoing thorny relationship between structure and agency, the book highlights the messy and interrelated ways in which children's everyday micro lives are influenced by wider macro structures." -- Provided by publisher
1.Introduction -- 2.Becoming and Being: Developments in the Sociology of Childhood -- 3.Macro Childhoods: Prioritising Structure -- 4.Micro Childhoods: Prioritising Agency -- 5.From Rights to Citizenship: Transformations and Constraints -- 6.Bridging Structure and Agency: Bringing in Inter- and Intra-generagency -- 7.Conclusions: Blurred Boundaries.
Includes bibliographical references (pages 155-169) and index.
Keywords: Children; Children -- Social conditions